Optimal honeynet configuration in enterprise computer networks - Yuriy V Aleinov; Ivan N Saushkin (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2013)
The article is devoted to the optimal conﬁguration of honeypots in the enterprise network. It describes the mathematical model of an enterprise computer network with honeypots. The authors analyze the standard ways of setting up honeypot parameters and propose the optimization criterion with regard to the dynamics of the external environment. The optimization problem of conﬁguring decoys is reviewed and the solution of the problem is discussed. Also a procedure of searching optimal honeypot conﬁguration is proposed and recommendations concerning practical appliance of the obtained results are given.